Transition Metal (Co, Ni, Fe, Cu) Single‐Atom Catalysts Anchored on 3D Nitrogen‐Doped Porous Carbon Nanosheets as Efficient Oxygen Reduction Electrocatalysts for Zn–Air Battery - Zhang, Mengtian; Li, Hao; Chen, Junxiang; Ma, Fei‐Xiang; Zhen, Liang; Wen, Zhenhai; Xu, Cheng‐Yan (Small (Weinheim an der Bergstrasse, Germany), 2022)
Exploring highly active and cost‐efficient single‐atom catalysts (SACs) for oxygen reduction reaction (ORR) is critical for the large‐scale application of Zn–air battery. Herein, density functional theory (DFT) calculations predict that the intrinsic ORR activity of the active metal of SACs follows the trend of Co > Fe > Ni ≈ Cu, in which Co SACs possess the best ORR activity due to its optimized spin density. Guided by DFT calculations, four kinds of transition metal single atoms embedded in 3D porous nitrogen‐doped carbon nanosheets (MSAs@PNCN, M = Co, Ni, Fe, Cu) are synthesized via a facile NaCl‐template assisted strategy. The resulting MSAs@PNCN displays ORR activity trend in lines with the theoretical predictions, and the Co SAs@PNCN exhibits the best ORR activity (E1/2 = 0.851 V), being comparable to that of Pt/C under alkaline conditions. X‐ray absorption fine structure (XAFS) spectra verify the atomically dispersed Co‐N4 sites are the catalytically active sites. The highly active CoN4 sites and the unique 3D porous structure contribute to the outstanding ORR performance of Co SAs@PNCN. Furthermore, the Co SAs@PNCN catalyst is employed as cathode in Zn–air battery, which can deliver a large power density of 220 mW cm–2 and maintain robust cycling stability over 530 cycles. Four kinds of transition metal single atoms embedded in 3D porous nitrogen‐doped carbon nanosheets (MSAs@PNCN, M = Co, Ni, Fe, Cu) are constructed via a facile NaCl‐template assisted strategy. The Co SAs@PNCN catalysts demonstrate remarkable performance with a half‐wave potential of 0.851 V for oxygen reduction reaction and a large power density of 220 mW cm–2 toward Zn–air battery.